Mosaic patterns of B‐vitamin synthesis and utilization in a natural marine microbial community - Laura Gómez‐Consarnau; Rohan Sachdeva; Scott M. Gifford; Lynda S. Cutter; Jed A. Fuhrman; Sergio A. Sañudo‐Wilhelmy; Mary Ann Moran (Environmental Microbiology, 2018)
Summary Aquatic environments contain large communities of microorganisms whose synergistic interactions mediate the cycling of major and trace nutrients, including vitamins. B‐vitamins are essential coenzymes that many organisms cannot synthesize. Thus, their exchange among de novo synthesizers and auxotrophs is expected to play an important role in the microbial consortia and explain some of the temporal and spatial changes observed in diversity. In this study, we analyzed metatranscriptomes of a natural marine microbial community, diel sampled quarterly over one year to try to identify the potential major B‐vitamin synthesizers and consumers. Transcriptomic data showed that the best‐represented taxa dominated the expression of synthesis genes for some B‐vitamins but lacked transcripts for others. For instance, Rhodobacterales dominated the expression of vitamin‐B 12 synthesis, but not of vitamin‐B 7 , whose synthesis transcripts were mainly represented by Flavobacteria. In contrast, bacterial groups that constituted less than 4% of the community (e.g., Verrucomicrobia) accounted for most of the vitamin‐B 1 synthesis transcripts. Furthermore, ambient vitamin‐B 1 concentrations were higher in samples collected during the day, and were positively correlated with chlorophyll‐ a concentrations. Our analysis supports the hypothesis that the mosaic of metabolic interdependencies through B‐vitamin synthesis and exchange are key processes that contribute to shaping microbial communities in nature .

Genome and epigenome of a novel marine Thaumarchaeota strain suggest viral infection, phosphorothioation DNA modification and multiple restriction systems - Nathan A. Ahlgren; Yangyang Chen; David M. Needham; Alma E. Parada; Rohan Sachdeva; Vickie Trinh; Ting Chen; Jed A. Fuhrman (Environmental Microbiology, 2017)
Summary Marine Thaumarchaeota are abundant ammonia‐oxidizers but have few representative laboratory‐cultured strains. We report the cultivation of Candidatus Nitrosomarinus catalina SPOT01, a novel strain that is less warm‐temperature tolerant than other cultivated Thaumarchaeota. Using metagenomic recruitment, strain SPOT01 comprises a major portion of Thaumarchaeota (4–54%) in temperate Pacific waters. Its complete 1.36 Mbp genome possesses several distinguishing features: putative phosphorothioation (PT) DNA modification genes; a region containing probable viral genes; and putative urea utilization genes. The PT modification genes and an adjacent putative restriction enzyme (RE) operon likely form a restriction modification (RM) system for defence from foreign DNA. PacBio sequencing showed >98% methylation at two motifs, and inferred PT guanine modification of 19% of possible TGCA sites. Metagenomic recruitment also reveals the putative virus region and PT modification and RE genes are present in 18–26%, 9–14% and

Beta diversity of marine bacteria depends on temporal scale - Stephen M. Hatosy; Jennifer B. H. Martiny; Rohan Sachdeva; Joshua Steele; Jed A. Fuhrman; Adam C. Martiny (Ecology, 2013)
Factors controlling the spatial distribution of bacterial diversity have been intensely studied, whereas less is known about temporal changes. To address this, we tested whether the mechanisms that underlie bacterial temporal β‐diversity vary across different scales in three marine microbial communities. While seasonal turnover was detected, at least 73% of the community variation occurred at intra‐seasonal temporal scales, suggesting that episodic events are important in structuring marine microbial communities. In addition, turnover at different temporal scales appeared to be driven by different factors. Intra‐seasonal turnover was significantly correlated to environmental variables such as phosphate and silicate concentrations, while seasonal and interannual turnover were related to nitrate concentration and temporal distance. We observed a strong link between the magnitude of environmental variation and bacterial β‐diversity in different communities. Analogous to spatial biogeography, we found different rates of community changes across temporal scales.

Population ecology of nitrifying Archaea and Bacteria in the Southern California Bight - J. Michael Beman; Rohan Sachdeva; Jed A. Fuhrman (Environmental Microbiology, 2010)
Summary Marine Crenarchaeota are among the most abundant microbial groups in the ocean, and although relatively little is currently known about their biogeochemical roles in marine ecosystems, recognition that Crenarchaeota posses ammonia monooxygenase ( amoA ) genes and may act as ammonia‐oxidizing archaea (AOA) offers another means of probing the ecology of these microorganisms. Here we use a time series approach combining quantification of archaeal and bacterial ammonia oxidizers with bacterial community fingerprints and biogeochemistry, to explore the population and community ecology of nitrification. At multiple depths (150, 500 and 890 m) in the Southern California Bight sampled monthly from 2003 to 2006, AOA were enumerated via quantitative PCR of archaeal amoA and marine group 1 Crenarchaeota 16S rRNA genes. Based on amoA genes, AOA were highly variable in time – a consistent feature of marine Crenarchaeota – however, average values were similar at different depths and ranged from 2.20 to 2.76 × 10 4 amoA copies ml −1 . Archaeal amoA genes were correlated with Crenarchaeota 16S rRNA genes ( r 2 = 0.79) and the slope of this relationship was 1.02, demonstrating that the majority of marine group 1 Crenarchaeota present over the dates and depths sampled possessed amoA . Two AOA clades were specifically quantified and compared with betaproteobacterial ammonia‐oxidizing bacteria (β‐AOB) amoA genes at 150 m; these AOA groups were found to strongly co‐vary in time ( r 2 = 0.70, P r 2 = 0.87, P